2019
DOI: 10.1001/jamainternmed.2019.2407
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as Adjunctive Therapy for Chronic Stable Angina

Abstract: The effects of acupuncture as adjunctive treatment to antianginal therapies for patients with chronic stable angina are uncertain. OBJECTIVE To investigate the efficacy and safety of acupuncture as adjunctive therapy to antianginal therapies in reducing frequency of angina attacks in patients with chronic stable angina. DESIGN, SETTING, AND PARTICIPANTS In this 20-week randomized clinical trial conducted in outpatient and inpatient settings at 5 clinical centers in China from October 10, 2012, to September 19,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 31 publications
2
136
0
1
Order By: Relevance
“…Zu diesem Zweck wertete sie insbesondere systematische Reviews mit Metaanalysen aus, darunter insgesamt 159 qualitativ hochwertige Cochrane-Reviews [49]. Im letzten Jahrzehnt wurden in China zunehmend hochwertige RCT-Studien zur Wirksamkeit von Akupunktur bei großen Patientenpopulationen mit unterschiedlichen Erkrankungen durchgeführt, u. a. eine negative Studie beim polyzystischen Ovarsyndrom [50], eine positive Studie bei schwerer funktionaler Obstipation [51], eine positive Studie bei Stressharninkontinenz [52], eine positive Studie bei klimakterischen Beschwerden mit einem klinisch nicht relevanten Effekt [53] und eine positive Studie bei stabiler Angina-Pectoris-Symptomatik [54].…”
Section: Akupunktur Bei Anderen Erkrankungenunclassified
“…Zu diesem Zweck wertete sie insbesondere systematische Reviews mit Metaanalysen aus, darunter insgesamt 159 qualitativ hochwertige Cochrane-Reviews [49]. Im letzten Jahrzehnt wurden in China zunehmend hochwertige RCT-Studien zur Wirksamkeit von Akupunktur bei großen Patientenpopulationen mit unterschiedlichen Erkrankungen durchgeführt, u. a. eine negative Studie beim polyzystischen Ovarsyndrom [50], eine positive Studie bei schwerer funktionaler Obstipation [51], eine positive Studie bei Stressharninkontinenz [52], eine positive Studie bei klimakterischen Beschwerden mit einem klinisch nicht relevanten Effekt [53] und eine positive Studie bei stabiler Angina-Pectoris-Symptomatik [54].…”
Section: Akupunktur Bei Anderen Erkrankungenunclassified
“…The blinding of acupuncturists is quite di cult to achieve. [41] Therefore, only patients, outcome assessors, and statisticians will be fully blind in this study.…”
Section: Blindingmentioning
confidence: 99%
“…Increasing experimental and clinical evidences have confirmed EA's effectiveness on cardiovascular diseases Ji et al, 2018;Huang et al, 2014;Fu et al, 2014;Zeng et al, 2018;Lu et al, 2016). A very recent article (Zhao et al, 2019) collected a total of 1651 patients with chronic stable angina and performed a clinical trial with acupuncture treatment. This study has shown that acupuncture as an auxiliary treatment method can alleviate clinical pain in patients with chronic stable angina, reduce the patient's anxiety and depression, and eventually improve the quality of life for these patients.…”
Section: Introductionmentioning
confidence: 99%